Uso de la fitohotmona vegetal con tres diferentes dosificaciones en la bellota del cultivo de orito (Musa spp) en el cantón La Maná. - De la Cruz Tapuyo, Marcos (2015)
This research was conducted in the province of Cotopaxi Canton La Mana and took place in the Hacienda Debray owned by Mr. Debray Yepez. Field work lasted ninety days starting from the onset of the acorn on the ground to harvest that was where the various developments was conducted to determine whether differences in the bunch when we bring a dose of plant phytohormone to the plant. As factor studied the application of gibberellic acid (GA3) in growing bananas had orito, experimental design used was an Experimental Design Randomized Complete Block "(RCBD) with 4 treatments and 5 repetitions. Each experimental unit consists of 10 floors, to determine differences between treatment means, the multiple range test of Tukey I was used at 95%. The study determined that bring you plant phytohormone the plant the fruit weight is increased owe the fruit gets more weight through grade and length of the fingers, thus obtaining a greater number of box 52 boxes / treatment on average with the application of phytohormone with doses of 1.5 mL / L-1, the other two application rates also exceeded the control treatment but to a lesser extent. The ratio and the decline also corroborate the positive reaction of the application of plant phytohormone so an increase in the ratio in treatments phytohormone equally be applied he was a reduction in the decline is appreciated as it was a better use of the fruit have a weight, grade and long finger more uniform.